Avaliação da ocorrência de ramificações dos canais mandibulares em regiões afetadas ou não por inflamação por meio de tomografia computadorizada de feixe cônico - Mauricio Augusto Aquino de Castro (2016)
The mandibular canal must be considered in several dental procedures in order to avoid injuries of the alveolar inferior nerve. The occurrence of anatomical variations of the mandibular canal increases the risk of neurovascular injuries. An increased sensitivity and failed anesthetic procedures in mandibles, especially in cases with inflammation, can be also related with alterations of the local innervation. This studyaimed to assess the occurrence of mandibular canal branching (MCB) in alveolar ridges affected by dental inflammation by means of cone beam computed tomography (CBCT), in order to verify if there is some relationship between MCB and dental inflammation. A database of 2,484 CBCTs was reviewed for identifying mandibular canal branching (MCB) and dental inflammation in mandibular alveolar ridges. The final sample was matched by age and gender. MCB nearby the posterior teeth was considered as the dependent variable. Dental inflammation occurrenceand location as well as measurements of gray levels at the same region were assessed as independent variables. The Kolmogorov-Smirnov, Chi-square, T-test and multiple logistic regression analysis were applied to verify the statistical relationship of the data (P<0.05). The most frequent inflammatory lesion was apical radiolucency with endodontic origin. The lesions mostly related to MCB were combined endodontic and periodontal lesions and apical lesions. Gender had no influence on mandibular canal branching (P=0.308), not did age (P=0.728). Theoccurrence of dental inflammation increased the risk for occurrence of the MCB nearby posterior teeth (P<0.001; OR=11.640; CI-95% 4.327-31.311). The gray levels had a minor role on the presence of MCB (P=0.002; OR=1.002; CI95% 1.002-1.003). The lesions most often associated with the branches had endodontic origin. An association between MCB situated around the posterior teeth and dentalinflammation was found.